Integrating AI·IoT-OAHPs with existing elderly care systems - Yanyi Wu (Digital Health)
This letter addresses the integration of artificial intelligence and the Internet of Things-based older adult healthcare programs with existing community and institutional elderly care systems. It highlights the current disconnect leading to service duplication and resource inefficiencies, proposes multifaceted integration approaches, and underscores the importance of supportive policies. International examples are referenced to demonstrate successful models, emphasizing the need for coordinated care to enhance service delivery and optimize resource use.